Chlorhexidine-encapsulated mesoporous silica-modified dentin adhesive. (November 2018) - Yan, Huiyi; Wang, Shilei; Han, Lin; Peng, Wenan; Yi, Luyao; Guo, Rui; Liu, Siying; Yang, Hongye; Huang, Cui
Abstract: Objectives: This work aims to explore the feasibility of chlorhexidine-encapsulated mesoporous silica (CHX@pMSN) as a modifier of a commercial dental adhesive via the evaluation of physicochemical properties and antibacterial capabilities of adhesive–dentin interface. Methods: Therapeutic adhesives were developed in the present study by incorporating CHX@pMSN into a commercial adhesive at four mass fractions (0, 1, 5 and 10 wt.%). The antibacterial capability on Streptococcus mutans (S. mutans) biofilm, conversion degree, adhesive morphology, microtensile bond strength (MTBS) and nanoleakage expression were evaluated comprehensively. Results: MTT and CLSM evaluation showed that CHX@pMSN-doped adhesive inhibits S. mutans biofilm growth, while CHX is released from the modified adhesive continuously. The incorporation of CHX@pMSN did not affect immediate bond strength at the concentration of 1% and 5% ( P > 0.05). Moreover, these bonds were mainly preserved in 5% CHX@pMSN group after one month of collagenase ageing. Meanwhile, CHX@pMSN-doped adhesive groups exhibited similar nanoleakage distribution compared with the control. Conclusion: This study showed that the 5% CHX@pMSN-modified adhesive achieved balance amongst unaffected immediate bonding strength, well-preserved bonds against collagenase ageing and effective inhibition of S. mutans biofilm growth. Clinical significance: CHX@pMSN-modified dentin adhesive can potentially extend the service life of adhesive restoration in clinic.